(untitled) (Research, Society and Development, 2023)
Introduction: Diabetes Mellitus (DM) is a condition defined by high levels of blood glucose, being a very prevalent disease nowadays. Among its numerous pathophysiological interactions, musculoskeletal complications emerge as a large percentage of outpatient complaints, especially those that manifest in the hands, due to the fact that they compromise the quality of life of patients. Objective: This study aimed to evaluate the clinical, epidemiological and pathophysiological aspects of musculoskeletal complications of the hands in patients with DM, supporting the construction of knowledge based on case reports and published articles. Materials and Methods: This is an integrative literature review about musculoskeletal disorders concomitant with diabetes mellitus. The PICO strategy was used to prepare the guiding question. Furthermore, the descriptors “Musculoskeletal Diseases” were crossed; “Diabetes Mellitus”; “Complications”, in the National Library of Medicine (PubMed MEDLINE), Scientific Electronic Library Online (SCIELO), Ebscohost, Google Scholar and Virtual Health Library (BVS) databases. Results and Discussion: DM is a well-characterized cause for the development of musculoskeletal diseases, such as chiropractic, Dupuytren’s contracture, trigger finger and others, highlighting the need to establish adequate therapy to prevent the progression of these and other complications. Conclusion: The conditions described directly impact the lives of patients, limiting their daily activities and compromising their quality of life. These conditions require an active search, aiming to identify them early, in addition to serving as a parameter for the evaluation of established therapy for DM.